2009
DOI: 10.1111/j.1751-228x.2008.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Building Research Collaboratives Among Schools and Universities: Lessons From the Field

Abstract: -In a previous issue of Mind, Brain, and Education , Hinton and Fischer (2008) argue that educational research needs to be grounded in the lived realities of school life. They advocate for research schools as a venue for accomplishing this. The Center for the Study of Boys ' and Girls ' Lives represents an alternative model -a research collaborative among independent schools and university-based scholars. This article describes the Center ' s experience with democratic, participatory action research. It disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…This means that theoretical research from one field can inform and shape empirical research in other disciplines (Willingham & Lloyd, ), such as education and psychology's constructivism finding new validation in neuroscience's neuroconstructivism (Mareschal et al, ; Szűcs & Goswami, ). It is clear that pedagogy can also inform theories in psychology and neuroscience (LaRusso et al, ) and test the applicability of neuroscience and psychology theories in the real world (Kuriloff et al, ; Stafford‐Brizard et al, ), just as psychology can help explain how and why some practices foster learning and development, while others do not (Ansari & Coch, ; Christodoulou & Gaab, ). For example, Sigman et al () described how an understanding of the neuroscience of visual learning could have predicted the superiority of a letter‐by‐letter “phonics” system over the whole word approach to the teaching of reading, saving the field a decades‐long debate (e.g., Castles et al, ).…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that theoretical research from one field can inform and shape empirical research in other disciplines (Willingham & Lloyd, ), such as education and psychology's constructivism finding new validation in neuroscience's neuroconstructivism (Mareschal et al, ; Szűcs & Goswami, ). It is clear that pedagogy can also inform theories in psychology and neuroscience (LaRusso et al, ) and test the applicability of neuroscience and psychology theories in the real world (Kuriloff et al, ; Stafford‐Brizard et al, ), just as psychology can help explain how and why some practices foster learning and development, while others do not (Ansari & Coch, ; Christodoulou & Gaab, ). For example, Sigman et al () described how an understanding of the neuroscience of visual learning could have predicted the superiority of a letter‐by‐letter “phonics” system over the whole word approach to the teaching of reading, saving the field a decades‐long debate (e.g., Castles et al, ).…”
Section: Strengthsmentioning
confidence: 99%
“…Grounding of research questions and hypotheses in real-world observations/need can increase impact of findings (Booth et al, 2015) Increased ethical considerations, compared to university-based research (Felzmann, 2009) Exposure to latest thinking/techniques (Jyrhämä et al, 2008), and latest research from other disciplines Increased logistical considerations (Felzmann, 2009;Plummer et al, 2014) Psychology and neuroscience can inform classroom pedagogy (Pickering & Howard-Jones, 2007;Rayner, Foorman, Perfetti, Pesetsky, & Seidenberg, 2001;Roediger, 2013;Stern, 2005;Thomas, Kovas, Meaburn, & Tolmie, 2015) Increased difficulty controlling extraneous variables, compared to lab-based research (Plummer et al, 2014) Pedagogy can inform psych/neurotheories (LaRusso et al, 2016) and test the applicability of theories in the real world (Kuriloff, Reichert, Stoudt, & Ravitch, 2009;Stafford-Brizard et al, 2017) Increased time commitments can be required for all parties to collaborate more closely (Simmonds, 2014) Psychological theories can be informed by neuroscience (Ochsner & Lieberman, 2001) Additional training for teachers and researchers can be required, sometimes requiring both time and funding (Ansari & Coch, 2006;Atkinson, 2017;Blake & Gardner, 2007;Simmonds, 2014) Psychological and neuroscientific findings can support educational theories and debates (Castles, Rastle, & Nation, 2018;Kim & Sung, 2013;Sigman, Peña, Goldin, & Ribeiro, 2014) Teachers can feel less confident to contribute to project formation (Simmonds, 2014) as they are often unable to access the original research papers from each discipline (Stafford-Brizard et al, 2017) Can provide a framework to empirically test teachers' ideas/pedagogical methods more objectively (Churches & McAleavy, 2015) Can develop desirable "teacher-researcher-practitioner model" for educators (Glennon, Hinton, Callahan, & Fischer, 2013) Opportunities Threats…”
Section: Strengths Weaknessesmentioning
confidence: 99%
“…The "Catch 22" of Time As in other CAR studies (Goodnough, 2008;Kuriloff et al, 2009;Watkins, 2006), the teacher researchers identified time as the number one challenge. While they had been given release time to plan and disseminate, there simply was not enough of it.…”
Section: Meaningful Professional Developmentmentioning
confidence: 99%
“…In these institutions, researchers work alongside doctors to incorporate recent advances in medical research into practice and track results. There is a growing movement in the field of education to create analogous institutions in education called research schools (Chen, ; Fischer, ; Hinton, ; Hinton & Fischer, , ; Kuriloff, Richert, Stoudt, & Ravitch, ). Research schools are living laboratories where researchers collaborate with practitioners to carry out research, train educators, and disseminate findings.…”
mentioning
confidence: 99%